1993
DOI: 10.1021/es00044a016
|View full text |Cite
|
Sign up to set email alerts
|

Oxocarboxylic and .alpha.,.omega.-dicarboxylic acids: photooxidation products of biogenic unsaturated fatty acids present in urban aerosols

Abstract: Oxocarboxylic and , -dicarboxylic acids in the free and salt form have been determined in airborne and nearground particles in an urban coastal area in the eastern Mediterranean Sea. They range from Ce to C26, with a maximum concentration at C9 and Ce. The sum of the concentrations of Ce and C9, --and , -dicarboxylic acids, represents an important proportion (10-36%) of the acidic fraction of aeolian particulates extracts. The compounds Ce and C•? are believed to be photooxidation products of anthropogenic cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0
8

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 14 publications
3
100
0
8
Order By: Relevance
“…In addition to DCAs (C 2di -C 9di ), many other intermediates and photochemically stable compounds are likely produced from the OH-induced degradation of oleic acid in aqueous solution. For atmospheric aerosols, some authors reported the photoproduction of C 9 , ωC 9 , C 9di and C 9ald , as well as nitrated carboxylic acids from the reaction of oleic acid with OH, O 3 or NO 3 [12,13,14,15,16]. In this study, C 9 and C 9ald could not be determined using our GC/FID technique.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…In addition to DCAs (C 2di -C 9di ), many other intermediates and photochemically stable compounds are likely produced from the OH-induced degradation of oleic acid in aqueous solution. For atmospheric aerosols, some authors reported the photoproduction of C 9 , ωC 9 , C 9di and C 9ald , as well as nitrated carboxylic acids from the reaction of oleic acid with OH, O 3 or NO 3 [12,13,14,15,16]. In this study, C 9 and C 9ald could not be determined using our GC/FID technique.…”
mentioning
confidence: 67%
“…The reaction of oleic acid (cis-9-octadecenoic, 9C 18 ) with O 3 , OH and NO 3 has recently emerged as a model system to better understand the photooxidation processes affecting unsaturated fatty acids in atmospheric aerosols [11,12]. Oleic acid is degraded through an oxidative cleavage of its double bond to produce C 9 compounds, i.e., nonanoic (C 9 ), 9-oxononanoic (ωC 9 ) azelaic (C 9di ) acids and 1-nonanal (C 9ald ) [13,14,15,16] as well as nitrated carboxylic acids [12]. Secondary photooxidation reactions could initiate the production of lower molecular weight DCAs such as C 2di -C 8di [9,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…We also found greater levels of azelaic (C 9 ) acid (28 ng m -3 ) at night than mid-day (24 ng m -3 ). C 9 is a specific oxidation product of unsaturated fatty acids (Kawamura and Gagosian, 1987;Stephanou and Stratigakis, 1993;Yokouchi and Ambe, 1986).…”
Section: α-Dicarbonylsmentioning
confidence: 99%
“…C 6 diacid is formed by the ozone oxidation of cyclohexene (Grosjean et al, 1978;Hatakeyama et al, 1987). On the other hand, C 9 is produced by the oxidation of biogenic unsaturated fatty acids (Kawamura and Gagosian, 1987;Stephanou and Stratigakis, 1993). Thus C 6 /C 9 ratio has been utilized as a tracer to estimate the anthropogenic v.s.…”
Section: Diurnal Variations Of Dicarboxylic Acids Oxocarboxylic Acidmentioning
confidence: 99%
“…Other than primary vehicular emissions and secondary sources, biogenic contributions of dicarboxylic acids are common, especially in rural areas. As azelaic acid (C 9 ) has been proposed as one of the reaction products by ozonolysis of biogenic unsaturated fatty acids (Kawamura and Kaplan, 1983;Yokouchi and Ambe, 1986;Kawamura and Gagosian, 1987;Stephanou and Stratigakis, 1993) and adipic acid (C 6 ) has been proposed as one of the products by oxidation of anthropogenic cyclohexene (Grosjean et al, 1978;Hatakeyama et al, 1987;Kawamura and Ikushima, 1993), the C 6 /C 9 ratio can be used as a potential indicator to show the strength of biogenic sources.…”
Section: Introductionmentioning
confidence: 99%